Molecular Communication Channel Modelling in FPGA Technology - Romanchenko, Daniil; Tartie, Matis; Que Le, Ba; Torres Gómez, Jorge; Dressler, Falko (Electronic Communications of the EASST, 2021)
Molecular Communication (MC) is a new paradigm for communication processes with a variety of applications such as health care and industrial sectors. The rapid development of MC, with the support of testbeds and simulators, requires scalable modeling tools. In this paper, we propose a field-programmable gate array (FPGA) design-based approach for the emission, diffusion, and reception of molecules. Results exhibit a close correspondence to state of the art analytical modeling of MC processes.